2016
DOI: 10.11604/pamj.2016.24.1.8382
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and risk factors of preterm births in a tertiary center in Lagos, Nigeria

Abstract: IntroductionPreterm birth is a dire complication of pregnancy that poses huge long-term medical and financial burdens for affected children, their families, and the health care system. The aim of the present study was to identify characteristics associated with preterm births at the Lagos University Teaching Hospital (LUTH), Lagos, Nigeria from 2011 to 2013.MethodsWe obtained Information from 5,561 maternal, fetal/neonatal and obstetric records from the labor ward. We excluded delivery at less than 22 weeks (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
77
4
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 33 publications
18
77
4
5
Order By: Relevance
“…This finding agrees with studies done in Nigeria [12], Tanzania [14] and other study [15] which found that advanced maternal age was significantly and independently increased the risk of preterm birth. Mothers in their advanced age (≥35 years), become weak and the uterine environment become less favorable for the growing fetus to provide maximum requirements thus predisposes them to be born before the due date.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with studies done in Nigeria [12], Tanzania [14] and other study [15] which found that advanced maternal age was significantly and independently increased the risk of preterm birth. Mothers in their advanced age (≥35 years), become weak and the uterine environment become less favorable for the growing fetus to provide maximum requirements thus predisposes them to be born before the due date.…”
Section: Discussionsupporting
confidence: 93%
“…The study revealed that hypertension during pregnancy was a significant risk factor for preterm birth. This result is in line with studies carried out in Ethiopia [13] [26] Nigeria [12] and Iran [21] who found that hypertension as a significant risk factor for preterm birth. Hypertension during pregnancy greatly reduces placental blood flow and leads to fetal restriction and poor growth resulting in obstetric emergencies which requires surgical delivery or induced preterm delivery as a lifesaving measure for both the mother and the fetus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From determinants of PTB, PROM [12,13,15,19,96,97], APH [13,15,19], ANC status [12,13,19], PIH [13,19,97], History of PTB [11,13,19], maternal age [13,15,97] multiple pregnancy [13,15,96] was prevalent in other African countries. The possible reason for this could be poor management of maternal health problems, limited access to health facilities and low health seeking behavior of the community.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Butali et al in 2015 in Nigeria found that babies with birth weight <1500 grams of 20.9%, and birth weight ranging from 1500 to <2500 grams by 41.8% . 7 In 2012, a study in United States of America, found incidence of preterm infants birth as much as 11.55% , of which 7.9% were of low birth weight. In addition, 2% of babies were born at very young pregnancies, and 1.42% with very low birth weight babies.…”
Section: Characteristics Of Preterm Birth Based On Birth Weightmentioning
confidence: 99%